Dynamic Pattern of Interleukin-1beta and -10 in Cerebrospinal Fluid following Aneurysmal Subarachnoid Hemorrhage - Yesaya Yunus; Julius July; Andi Asadul Islam; Eka Julianta Wahjoepramono; Irawan Yusuf (The Prodia Education and Research Institute (PERI), 2014)
BACKGROUND: Inflammation following aneurysmal subarachnoid hemorrhage (SAH) is associated with patient outcome. This study aimed to analyze the dynamics pattern of the pro-inflammatory interleukin (IL)-1β and anti-inflammatory cytokine IL-10 in the cerebrospinal fluid (CSF) following aneurysmal SAH.METHODS: This is a prospective observational study. The CSF was collected prior to surgery, and on the 2nd, 4th and 6th days after surgery. The CSF was then analyzed for IL-1β and -10 using enzyme-linked immunosorbent assay. Delayed Ischemic Neurological Deficits (DIND) was determined based on new neurological deficits within the first week after surgery. Data was analysed with T test or Wilcoxon Rank-Sum test to evaluate the pattern of biomarkers between DIND and non-DIND groups.RESULTS: There were 33 patients enrolled in this study, 16 patients (48.48%) who experienced DIND and 17 patients (51.52%) were non-DIND. There were significant increase dynamic levels of IL-10 and -1β in DIND patients (p<0.05).CONCLUSION: Significant increase levels of IL-10 and -1β in CSF after aneurysmal SAH are associated with DIND.KEYWORDS: IL-1β, IL-10, DIND